Aplikasi Media pembelajaran huruf hijaiyah dengan metode bahasa bugis berbasis android - Masnur Masnur; Andi Wafiah; Hatma Hatma; Dian Megah Sari; Mughafir Yunus; Muhammad Rezky Rapi (Computer Science and Information Technology, 2023)
Children or parents need to understand hijaiyah letters more quickly, and we can see this from the many children and parents who do not understand the correct pronunciation of hijaiyah letters, especially for the Bugis community in South Sulawesi. For the Bugis community who want to learn to recognize hijaiyah letters correctly, anywhere and anytime, without having to think about coming to the recitation area or waiting for the recitation teacher to come to their house. Therefore, research was carried out by making an Android-based Buginese language learning media application with the aim of making it easier for dominant users to understand more about using the Bugis language so they can learn hijaiyah letters. The research method used is observation, literature, documentation and interviews. This application analysis and design tool uses the HTML, JavaScript, CSS and Apache Cordova programming languages ​​as the framework. While the application testing method is divided into two, namely BlackBox to test the functional application according to the algorithm and Whitebox to find out the logic of thinking according to the application flowchart. With this application, it is hoped that it will make it easier for someone to learn hijaiyah letters, a Bugis version is also available so that it makes it easier to understand hijaiyah letters, especially for the Bugis people.